Reporte de Pecari tajacu y Procyon lotor con anomalías cromáticas en el Estado de Guerrero, México - Ruiz-Gutiérrez, Fernando (2023)
This paper documents the first record of chromatic anomalies in Collared Peccary (Pecari tajacu) and the third in the Raccoon (Procyon lotor) for Mexico. The findings were made during monitoring conducted between 2009 and 2021, using camera traps, primarily in the Sierra Madre del Sur ecoregion of the state of Guerrero, Mexico. Procyon lotor was recorded between November 5th and December 1st, 2019, in riparian vegetation of a deciduous tropical forest (17°47’35”N, 98°39’59”W, 1134 m altitude). Meanwhile, Pecari tajacu was recorded on June 7th and July 22nd, 2021, in an abandoned crop clearing (17°38’12”N, 100°40’50”W; 1532 m altitude).